Studies on Groundwater Quality in Slums of Visakhapatnam, Andhra Pradesh - RAMAKRISHNA, CH.; MALLIKARJUNA RAO, D.; SUBBA RAO, K.; SRINIVAS, N. (Asian Journal of Chemistry, 2010)
Commensurate with the growth of industrial and allied activities in and around Visakhapatnam city, its area grew from 30 km2 in 1960 to over 80 km2 to date. The city's population according to 2001 census is about 1.33 million. Water supply has always been inadequate in this city with the crisis growing along with the cities progress. Today's water requirement is 360 million gallons per day. The existing Thatipudi, Gossthani, Meghadrigadda and Mudasarlova can hardly meet 50 % of the need. Raiwada water scheme can add a little more, therefore the supply capacity needs to be augmented. The only viable solution is to transport water from Godhavari. Apart from the municipal supply the population also depends upon the ground water reservoirs.